EFFECT OF YEAST CONCENTRATION AND TYPE ON BIOETHANOL PRODUCTION FROM SUGARCANE BAGASSE - Tuti Maryana; Devi Silsia; Budiyanto Budiyanto (BPFP Faperta UNIB, 2020)
Sugarcane bagasse is one of the potential biomass as raw material for bioethanol production. This study aims to determine the effect of concentration and type of yeast on the characteristics of bioethanol produced from bagasse bagel delignified with a mixture of NH4OH-NaOH in a ratio of 1:20. This study uses a Completely Randomized Design (CRD) with 2 factors: yeast concentration (0.4%, 0.6% and 0.8%) and the type of yeast (tape yeast and bread yeast). The results of this study indicate that Bioethanol levels increase with increasing yeast concentration. The highest levels of bioethanol were obtainedat the use of 0.8% bread yeast, ie 14.16%